Gangrenous bowel ischemia-a complication of COVID-19: a case report - Swami, Ganesh Ashok; Shinde, Swapnil Kashinath; S., Halnikar Chandrashekha; Asawa, Ganesh (International Surgery Journal, 2021)
The novel virus SARS-CoV2 responsible for ongoing pandemic of COVID-19 since March 2020 has not only been found to cause pneumonia but also involves multiple symptoms such as Gastroinstestinal system, central nervous system, cardiovascular system as a part of multi inflammatory syndrome, which has been increasingly recognized as a part of disease spectrum. COVID-19 associated coagulopathy has emerged as a major cause of high morbidity and mortality, one of which is result being ischemic bowel disease. So herein, we are going to present the first case of probable case of COVID-19 associated ischemic bowel disease in our institute.